Genetically-controlled Vesicle-Associated Membrane Protein 1 expression may contribute to Alzheimer’s pathophysiology and susceptibility - Sevlever, Daniel; Zou, Fanggeng; Ma, Li; Carrasquillo, Sebastian; Crump, Michael G.; Culley, Oliver J.; Hunter, Talisha A.; Bisceglio, Gina D.; Younkin, Linda; Allen, Mariet; Carrasquillo, Minerva M.; Sando, Sigrid B.; et al. (Springer, 2015)
Background